Early childhood memories of animals: reflections and considerations in relation to posthuman education - Suvilehto, Pirjo; Aerila, Juli-Anna (Routledge, Taylor & Francis Group, 2025)
This study focuses on literary arts education, especially childhood memories of pets and other more-than-humans. Memory writings were collected as data using the Pritney method among students in early childhood teacher education. The written memories were analysed through the lens of bibliotherapy. Practices with reflections provide also perspectives on posthumanities and offer a sense of wellbeing. Bibliotherapy approach and posthuman theory allow exploring our position as humans and more-than-humans in the educational system. Students (n = 200) are recalling their primary memories related to animal/pet contacts, toys, play, and characters in literature. Memories through close readings illuminate how the animal theme and bibliotherapy approach are employed in this project. Students may develop an awareness of the value of animal geographies and literary arts in education, thus moving towards posthuman education and fostering different ways of caring and wellbeing, ethics, and education that also encompass more-than-humans.